Unraveling the functional consequences of a novel germline missense mutation (R38C) in the yeast model of succinate dehydrogenase subunit B: insights into neurodegenerative disorders - Zheng, Jiatong; Liu, Siru; Wang, Dongdong; Li, Linlin; Sarsaiya, Surendra; Zhou, Hua; Cai, Heng (Frontiers in Molecular Neuroscience, 2023)
This study explores the implications of a novel germline missense mutation (R38C) in the succinate dehydrogenase (SDH) subunit B, which has been linked to neurodegenerative diseases. The mutation was identified from the SDH mutation database and corresponds to the SDH2R32C allele, mirroring the human SDHBR38C mutation. By subjecting the mutant yeast model to hydrogen peroxide (H2O2) stress, simulating oxidative stress, we observed heightened sensitivity to oxidative conditions. Quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR) analysis revealed significant regulation (P<0.05) of genes associated with antioxidant systems and energy metabolism. Through gas chromatography-mass spectrometry (GC-MS) analysis, we examined yeast cell metabolites under oxidative stress, uncovering insights into the potential protective role of o-vanillin. This study elucidates the biological mechanisms underlying cellular oxidative stress responses, offering valuable insights into its repercussions. These findings shed light on innovative avenues for addressing neurodegenerative diseases, potentially revolutionizing therapeutic strategies.